APPLICATION OF PROBLEM-BASED LEARNING MODEL TO IMPROVE STUDENT PARTICIPATION AND ACTIVITY IN ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION AT SMPN 3 2X11 KAYU TANAM - Anggraini, Tri Della (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to improve students’ participation and activeness in Islamic Religious Education and Character (PAI&BP) learning through the implementation of the Problem-Based Learning (PBL) model at SMPN 3 2x11 Kayu Tanam. Problem Based Learning was chosen because this model emphasizes active student involvement in solving real-world problems, encourages group collaboration, and trains critical thinking skills. The type of research used is Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 23 seventh-grade students. Data were collected through observation, documentation, and project assessments, then analyzed descriptively using qualitative methods with percentage calculations. The results of the study indicate that the implementation of PBL can improve the quality of the learning process. In the first cycle, student participation was still low, shown by a lack of confidence in asking questions, answering, and expressing opinions, as well as uneven group discussions. Learning outcomes were also limited, with only 52.2% of students meeting the Minimum Mastery Criteria (KKM). Based on the reflection of cycle I, improvements were made in cycle II, including clearer role assignments within groups, the use of guiding questions, and providing motivation and rewards for active students. These improvements had a positive impact, as evidenced by increased overall student engagement, a more conducive classroom atmosphere, and improved learning outcomes, with 87.0% of students achieving KKM. Thus, it can be concluded that the Problem-Based Learning (PBL) model is effective in increasing students’ participation, activeness, collaboration, and learning outcomes in PAI-BP learning. PBL can also serve as an innovative alternative learning model that is relevant for creating more interactive, meaningful, and student-centered learning.